Creating Legal Certainty for Victims: A Comparative Analysis of the Resolution of Past Gross Human Rights Violations Through Judicial and Non-Judicial Mechanisms - Ramadhan, Muhammad Iqbal; Ahmad, Suparji; Rifai, Anis (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Disputes in import-export businesses pose substantial challenges to the dynamics of global trade. This study examines the critical factors influencing dispute resolution methods, focusing on a comparative analysis of litigation and arbitration in the context of international trade. Employing a normative legal research methodology with a comparative approach, the study evaluates the strengths and weaknesses of each method. Key factors considered include the complexity of disputes, monetary value, confidentiality needs, the dynamics of the parties involved, and the potential impact on business relationships. The findings indicate that arbitration often provides a more flexible, efficient, and relationship-preserving solution than traditional litigation, though the optimal approach depends on the specific characteristics of each case. This study offers strategic insights for businesses navigating international trade disputes, underscoring the importance of adopting a tailored and measurable dispute resolution strategy.